The diagnosis of clinically significant oesophageal Candida infections: a reappraisal of clinicopathological findings. Issue 5 (21st April 2020) - Hissong, Erika; Schechter, Shula; Mowers, Jonathan; Yantiss, Rhonda K; Slavik, Tomas; Cheng, Jerome; Lamps, Laura W
Abstract : Aims: Distinguishing true oesophageal Candida infections from oral contaminants is a common diagnostic issue. Historically, histological features believed to indicate true infection included epithelial invasion by pseudohyphae and intraepithelial neutrophils. Whether or not these features correlate with endoscopic lesions, symptoms and response to therapy has never been tested in a large cohort. The aim of this study was to determine whether specific histological features correlate with clinical and endoscopic findings when Candida is found in oesophageal biopsies. Methods and results: We reviewed 271 biopsies in which Candida was detected. Cases were evaluated for the presence of desquamated epithelial cells, location/type of fungal forms, neutrophils, and ulceration. Medical records were reviewed for clinical history, endoscopic lesions, and response to antifungal therapy. Statistical analysis was used to determine whether any histological features significantly correlated with clinical variables. There were 120 males and 151 females with a mean age of 42 years. Fifty‐nine per cent had symptoms referable to the oesophagus, particularly dysphagia (36%). Most (73%) patients had abnormal endoscopic findings, with plaques, ulcers, or macroscopic evidence of oesophagitis. Seventy‐one per cent of patients with documented antifungal therapy showed symptomatic improvement. Overall, there was no statistically significant correlation between any histological feature and presenting symptoms, endoscopic findings, or response to therapy. Importantly, the lack of pseudohyphae, demonstrable invasion of intact epithelium or neutrophilic infiltrates did not exclude clinically significant infection. Conclusions: We conclude that detection of Candida in oesophageal biopsies is always potentially clinically significant. Treatment decisions should be made on the basis of an integration of clinical, endoscopic and histological findings.